Evaluasi Program Pusat Pembelajaran Keluarga (PUSPAGA) dalam Penanganan Anak Putus Sekolah di Kecamatan Wiyung - Febriana , Rosa Indah; Pramudiana, Ika Devi; Widyawati (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2024)
The Surabaya Family Learning Center (PUSPAGA) Program policy is under the auspices of the Office of Women's Empowerment and Child Protection as well as Population Control and Family Planning (DP3APPKB). This program aims to be a special place for Surabaya residents who want to overcome problems, both related to child delinquency and family problems. This research aims to describe and analyze the data as follows: 1) Assess the evaluation of the Family Learning Center (PUSPAGA) program in handling school dropouts in Wiyung Sub-district, Surabaya City; and 2) Assess the factors that support and hinder the Family Learning Center program in handling school dropouts in Wiyung Sub-district, Surabaya City. The research method used is descriptive qualitative, with evaluation indicators including effectiveness, efficiency, adequacy, equity, responsiveness, and fixity according to William N. Dunn. This research uses a qualitative approach with data collection techniques through interviews, documentation, and observation. The results showed that the policy evaluation of the PUSPAGA program in handling out-of-school children has been running well, but there are several aspects in the evaluation indicators that need to be improved which include several inhibiting factors such as: 1) The agency and the city government do not provide enough socialization to the community so that they are still unfamiliar with the presence of PUSPAGA itself; and 2) Parents' views on education, some of the education of parents whose children have dropped out of school are classified as low-educated parents.